1997
DOI: 10.1164/ajrccm.155.5.9154872
|View full text |Cite
|
Sign up to set email alerts
|

Functional impairment in lone cryptogenic fibrosing alveolitis and fibrosing alveolitis associated with systemic sclerosis: a comparison.

Abstract: Lone cryptogenic fibrosing alveolitis (CFA) is histologically identical to fibrosing alveolitis associated with systemic sclerosis (FASSc), but it has a much worse prognosis after matching for disease severity at presentation. Thin-section CT scanning (CT) provides a reproducible method of quantifying the morphologic extent of fibrosing alveolitis. The aim of this study was to gain insights into contrasting pathophysiologic mechanisms in the two diseases by comparing patterns of functional impairment after mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(35 citation statements)
references
References 0 publications
0
34
0
1
Order By: Relevance
“…Quantification of CT patterns and the relationship of the results to lung function abnormalities have been determined in a number of diffuse lung diseases, including idiopathic pulmonary fibrosis [22] and lung fibrosis associated with systemic fibrosis [23,24], sarcoidosis [25] and small airways disease [26,27]. The method of scoring of the reticular patterns, ground-glass opacification and nodules used in the current study has been previously shown to give good observer agreement [28].…”
Section: Discussionmentioning
confidence: 93%
“…Quantification of CT patterns and the relationship of the results to lung function abnormalities have been determined in a number of diffuse lung diseases, including idiopathic pulmonary fibrosis [22] and lung fibrosis associated with systemic fibrosis [23,24], sarcoidosis [25] and small airways disease [26,27]. The method of scoring of the reticular patterns, ground-glass opacification and nodules used in the current study has been previously shown to give good observer agreement [28].…”
Section: Discussionmentioning
confidence: 93%
“…39 Exercise tests may have a role in staging and monitoring disease; however, this has not been clearly defined. Exercise-induced changes in oxygenation during both maximal and submaximal tests have been associated with extent of ILD on biopsy and imaging, [52][53][54] indicating a relationship with disease severity. However, in patients with IPF, disease severity and progression can be effectively evaluated using spirometry and TLCO with 6 months' follow-up.…”
Section: When Should We Assess Exercise Capacity In Ild?mentioning
confidence: 99%
“…The quantification and interpretation of disease severity using pulmonary function tests in patients with IPF is often confounded by coexistent emphysema and results in a spurious preservation of lung volume and depression of gas transfer [30,31]. However, although pulmonary function tests usually show respiratory volumes and flows that are normal or subnormal, diffusing capacity of the lung for carbon monoxide (DLCO) is substantially reduced and exercise hypoxaemia is common (table 2).…”
Section: Clinical Featuresmentioning
confidence: 99%